La educación universitaria de la mujer - Campos Arenas, Agustín (2012)
The present article talks about the universityeducation of women in different countries, includingPeru. It shows the challenge that women are able toaccess to university education and the struggles thatwomen and men had to perform for the universityeducation are able for women.It includes names and dates, as an important elementin a story of woman education that could interest thereader.